Testing factors influencing handgrip strength and reaction time to visual stimulus in selected martial arts - Dariusz Bajkowski; Wojciech J. Cynarski (Journal of Kinesiology and Exercise Sciences)
Background: Handgrip strength (HGS) is essential in sports, including martial arts, as it can be used to evaluate general athletes’ performance and physical fitness. Reaction time (RT) is another characteristic that is of value in sports based on fast reaction instead of strength. The two measures belong to the same group of coordinative energetic abilities analyzed in sports theory. The available literature suggests that handgrip strength may depend on body weight but can also be affected by other parameters. Additionally, the athlete’s age and martial arts training can impact reaction time. Still, verifying whether the characteristics could be applied to martial arts athletes is crucial. Methods: Several characteristics, such as athletes’ body weight, age, years of training, and skills, were evaluated during a survey of 166 male jiu-jitsu athletes (modern jiu-jitsu) and karate (Shotokan, Kyokushin). HGS was measured based on the dynamometric approach, whereas reaction time was evaluated using Ditrich’s rod method. The data were analyzed using the hierarchical multiple regression method to identify the variables influencing HGS and RT. Furthermore, the classification and regression tree method was implemented to illustrate how variables used in the study influenced HGS or RT. Results: The present study demonstrated that athletes’ body weight is the most significant factor affecting the handgrip strength of male athletes trained in martial arts. It can explain 61% of the HGS variance. Regression analysis of factors influencing reaction time showed that martial arts are the factor that affects the characteristic. However, martial arts can explain up to 17% of the reaction time variance. Based on the classification and regression tree approach, it was shown that HGS depends primarily on athletes’ body weight rather than on their age, skills, and years of training. For reaction time, martial arts were the most significant factor distinguishing between jiu-jitsu and karate participants. The next factor affecting athletes’ classification was years of training. Conclusion: Based on the hierarchical multiple linear regression method and classification and regression tree approach, it was found that athletes’ body weight is the most influential factor affecting the handgrip strength of martial arts practitioners. Reaction time is affected by martial arts. However, using the classification and regression tree approach revealed that additional factors such as athletes’ age, years of training, or skills should be considered. Similarly, reaction time is also affected by years of training. Although our study showed that handgrip strength and reaction time are functions of other variables that can be easily evaluated in trainers’ practice, the two statistical methods cannot reveal the relationships between the variables, suggesting further studies in the field.